The Depiction of Violence in the Terrifier Film Series: Realism vs. Stylisation - Oliver Kohár, (Communication Today, 2025)
The Terrifier horror film series, despite its low-budget, has become a cult phenomenon and achieved unexpected commercial success. This study focuses on analysing the function of violence in contemporary horror cinema, specifically examining the relationship between realism and stylisation in violent scenes within the Terrifier films. The theoretical framework of this research explores violence as both a narrative and aesthetic element, as well as its evolution in modern horror films. The core of the study is the application of this knowledge in the form of discourse analysis on three scenes from the Terrifier film series. The analysis utilises qualitative methods of film study to determine the extent to which these scenes balance realistic depictions of violence and their stylised presentation. The findings of this study contribute to a broader discussion on violence in contemporary horror, its ability to shock and captivate audiences, and its role in testing the boundaries of viewer tolerance.